Cultural Communication from the Muhammadiyah Perspective - Pujiastuti, Yanti Lestari; Suherman, Muhammad Tanziil; Juliansyah, Aris; Effendie, Itsna Nurhayat (GoAcademica Research & Publishing, 2024)
Kasepuhan Sinarresmi is a traditional village that practices rice management rituals that treat rice like humans. This ritual is part of the Kasepuhan customs, in general the ritual carried out is in the form of greetings and permission from the pungpuhunan when carrying out farming activities. Meanwhile, Muhammadiyah is a religious movement that seeks to purify Islam's teachings according to the Qur’an, Hadith and Sunnah, which is far from heresy, superstition and khurofat. This research aims to: 1) find out how the ritual processes for treating rice are carried out by the residents of Kasepuhan Sinarresmi, 2) find out how the officials of the Muhammadiyah Tarjih and Tajdid Council interpret the rituals for treating rice carried out by the residents of Kasepuhan Sinarresmi and 3) find out what is the communication strategy in purifying Islamic religious teachings carried out by Muhammadiyah towards ethnic community groups. The method used is qualitative research with a phenomenological approach. The results of this research are: 1) there are 38 rituals which can be classified into 11 activity groups, namely: rituals before planting rice, rituals for planting rice, rituals for growing rice, rituals for caring for growing rice, rituals for harvesting rice, the ritual of storing rice, the ritual of cooking the first rice harvest, the ritual of resting huma land, Seren Taun, the ritual of restarting farming activities, and rituals related to the Islamic calendar, 2) Muhammadiyah does not reject local culture and considers cultural diversity to be the nation's wealth, 3) the da'wah strategy for ethnic communities is carried out using a multicultural da'wah method where the purification of Islamic teachings is carried out flexibly according to cultural space.